Scientific and educational component of strengthening the economic potential of the state - Melnyk, Victoriia; Pohrishchuk, Oleg; Prots, Andriy (Herald of Economics, 2024)
Introduction. The modern development of humanity is accompanied by significant social changes, which require the implementation of a number of transformations in the field of science and education, the study of the processes of socio-economic transformations, the creation of the necessary conditions for the training of highly qualified specialists in innovative development, the attraction of investments and the achievement of a high level of economic competitiveness. The purpose of the study is to substantiate the theoretical and methodological concept of the scientific and educational component of strengthening the economic potential of the state. Research methods. In the research process, special and general scientific methods were used, and a comprehensive approach was applied to uncovering the issue of scientific and educational support for the development and strengthening of the state’s economic potential. The results. It was determined that the economic development of the state is based on such a strategic resource as knowledge. The scientific and educational component plays a leading role in the formation of knowledge and skills, ensures the training of personnel capable of solving complex economic problems, generating new ideas and implementing them in the practice of economic activity. It is proved that the economic and intellectual potential of the state are interconnected and strengthen each other through the interaction of functional elements. An effective system of investment support for education and science contributes to the development of the intellectual potential of the state, which, in turn, is a stimulus for economic development, the introduction of innovations and the growth of labor productivity. Research has established that the main factors influencing the formation of economic potential include: market, political and legal, scientific and educational, resource, infrastructural, social and cultural factors. Ensuring optimal management of such potential based on consideration of influencing factors contributes to its strengthening and achieving sustainable development. The intellectualization of various spheres of human activity and society in general contributes to the expansion of opportunities for the realization of the economic potential of development. Functional provision of higher education is a system that determines its quality and compliance with modern requirements of the labor market and society in general. Perspectives. We consider it expedient to focus further research in this direction on the development of scientific approaches to the functioning of science and education in the modern space of social and economic development.